Murine Models of Splenic Marginal Zone Lymphoma: A Role for Cav1? - Patten, Chelsey L.; Cutucache, Christine E. (Frontiers in Oncology, 2016)
Dozens of murine models of indolent and aggressive B-cell lymphomas have been generated to date. These include those manifesting chronic lymphocytic leukemia (CLL), diffuse large B-cell lymphoma (DLBCL), as well as xenografts of mantle cell lymphoma (MCL). These models have led to an improved understanding of disease etiology, B-cell biology, immunomodulation, and the importance of the tumor microenvironment. Despite these efforts in CLL, DLBCL, and MCL, considerably little progress toward a model of splenic marginal zone lymphoma (SMZL) has been accomplished. Herein, we describe the similarities and differences between CLL, MCL, and SMZL and highlight effective murine models that mimic disease in the two former, in hopes of informing a potential model of the latter. At the time of writing this review, the precise molecular events of SMZL remain to be determined and a treatment regimen remains to be identified. Therefore, based on the efforts put forth in the B-cell lymphoma field throughout the past three decades, the established role of caveolin-1 in B- and T-cell biology as an oncogene or tumor suppressor, and the recurrent deletion or loss of heterozygosity (LOH) of 7q in many cancers, we make recommendations for a murine model of SMZL.